2016
DOI: 10.1002/alr.21760
|View full text |Cite
|
Sign up to set email alerts
|

Objective sinonasal functional outcomes in endoscopic anterior skull-base surgery: an evidence-based review with recommendations

Abstract: Based on the available evidence, nasoseptal flap (NSF) elevation with or without use in reconstruction likely leads to impairment in objective olfactory function. Endoscopic sellar and parasellar surgery without the elevation of an NSF may lead to a transient reduction in olfactory function. In the absence of a high a priori risk of cerebrospinal fluid (CSF) leak, it is an option to avoid routine NSF elevation in sellar and parasellar procedures, with preservation of at least 1 vascular pedicle during the appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…In a recent systematic review examining objective sinonasal outcomes including olfaction, mucociliary clearance, and nasal airflow, Greig et al identified 10 articles and concluded that NSF elevation led to impairment in olfactory function. The authors offer the option to avoid routine NSF elevation in sellar and parasellar procedures—and if a NSF is utilized, that the donor site defect reconstruction be considered . Lacking from these studies is a long‐term, prospective perspective of sinonasal QOL following NSF harvest in EASB surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent systematic review examining objective sinonasal outcomes including olfaction, mucociliary clearance, and nasal airflow, Greig et al identified 10 articles and concluded that NSF elevation led to impairment in olfactory function. The authors offer the option to avoid routine NSF elevation in sellar and parasellar procedures—and if a NSF is utilized, that the donor site defect reconstruction be considered . Lacking from these studies is a long‐term, prospective perspective of sinonasal QOL following NSF harvest in EASB surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The authors offer the option to avoid routine NSF elevation in sellar and parasellar procedures-and if a NSF is utilized, that the donor site defect reconstruction be considered. 36 Lacking from these studies is a long-term, prospective perspective of sinonasal QOL following NSF harvest in EASB surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Awad et al examined sinonasal morbidity after ESBS, but not specifically olfactory dysfunction . More recently, Thompson et al, Patel et al, and Greig et al all summarized key studies on olfactory outcomes after ESBS, but these were not comprehensive systematic reviews, and they did not perform a meta‐analysis …”
Section: Introductionmentioning
confidence: 99%
“…18 More recently, Thompson et al, Patel et al, and Greig et al all summarized key studies on olfactory outcomes after ESBS, but these were not comprehensive systematic reviews, and they did not perform a meta-analysis. 5,6,19 To date, no systemic review with meta-analysis has been performed to examine objective olfactory function after ESBS. Barriers to meta-analysis include potential differences in surgical technique, tumor histology, and olfactory testing.…”
Section: Introductionmentioning
confidence: 99%